2012
DOI: 10.1002/pro.2151
|View full text |Cite
|
Sign up to set email alerts
|

The PNT domain from Drosophila pointed‐P2 contains a dynamic N‐terminal helix preceded by a disordered phosphoacceptor sequence

Abstract: Pointed-P2, the Drosophila ortholog of human ETS1 and ETS2, is a transcription factor involved in Ras/MAP kinase-regulated gene expression. In addition to a DNA-binding ETS domain, Pointed-P2 contains a PNT (or SAM) domain that serves as a docking module to enhance phosphorylation of an adjacent phosphoacceptor threonine by the ERK2 MAP kinase Rolled. Using NMR chemical shift, 15 N relaxation, and amide hydrogen exchange measurements, we demonstrate that the Pointed-P2 PNT domain contains a dynamic N-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Ets proteins are subclassified by the presence of further domains associated with PPIs (protein–protein interactions) or transcriptional regulation [ 2 , 3 ], including the TCF (containing the B-box [ 6 ]) and PEA3 (containing the unstructured PEA3 transactivation domain [ 7 ]) subfamilies. PNT (pointed) domains are also frequently found N-terminal to the Ets domain, involved in PPI and homodimerization [ 8 , 9 ] ( Figure 1 A).…”
Section: Introductionmentioning
confidence: 99%
“…Ets proteins are subclassified by the presence of further domains associated with PPIs (protein–protein interactions) or transcriptional regulation [ 2 , 3 ], including the TCF (containing the B-box [ 6 ]) and PEA3 (containing the unstructured PEA3 transactivation domain [ 7 ]) subfamilies. PNT (pointed) domains are also frequently found N-terminal to the Ets domain, involved in PPI and homodimerization [ 8 , 9 ] ( Figure 1 A).…”
Section: Introductionmentioning
confidence: 99%
“…Although nuclear magnetic resonance (NMR)-derived structural ensembles of the Ets1 PNT domain and adjacent phosphoacceptors in their unmodified and modified forms have been reported, it was not fully established how phosphorylation induces conformational changes that lead to enhanced CBP binding. In particular, the NMR data are consistent with two models: (1) a 0 remains separate from a 1 , adopting a broad conformational distribution that points away from the SAM core; or (2) a 0 and a 1 form one continuous helix that is detached from this core bundle (Lau et al, 2012;Nelson et al, 2010). Furthermore, it is also not clear how the PNT and TAZ1 domains interact.…”
Section: Introductionmentioning
confidence: 72%
“…Ets1 is a member of the ETS family of transcription factors that are frequently used as downstream effectors in signal transduction cascades to regulate cell proliferation, differentiation, migration, and apoptosis (Hollenhorst et al, 2011;Sharrocks, 2001). Previous studies (Lau et al, 2012;Nelson et al, 2010) revealed that the increased transcriptional activity of Ets1 upon activation of the Ras/MAPK signaling pathway depends on the phosphorylation-enhanced binding of Ets1 to CBP/p300, which are paralog transcriptional coactivators that serve as scaffolds for the assembly of various transcription factors (Kasper et al, 2006). Specifically, the MAPK extracellular signal-regulated kinase 2 (ERK2) phosphorylates T38 and S41 in an ID N-terminal segment of Ets1, immediately adjacent to the folded PNT domain.…”
Section: Introductionmentioning
confidence: 99%
“…So in addition to the ETS DNA binding domain, the N‐terminal region of PntP2 harbors a SAM domain (also referred to as the Pointed domain). The core structure of the SAM domain of ETS1 and PntP2 is comprised of four α‐helices (H2–H5) and a fifth helix (H1), N‐terminal to this core (Figure b) (Lau, Okon, & McIntosh, ; Slupsky et al, ). The SAM domain of PntP2 and its vertebrate orthologs has been shown to mediate protein–protein interactions.…”
Section: Structural Organization and Regulation Of Pointedmentioning
confidence: 99%